The Larva and Advertisement Call of Bokermannohyla ahenea (Anura: Hylidae) - Garey, Michel; Provete, Diogo B.; Ouchi-Melo, Lilian S.; Haddad, Celio F. B.; Rossa-Feres, Denise de C. [UNESP] (Soc Brasileira Herpetologia, 2020)
Bokermannohyla ahenea is endemic to the Serra da Bocaina, a portion of the Serra do Mar in the Atlantic Forest of Southeastern Brazil. Little information is currently available about this species. Herein, we describe the larval morphology of B. ahenea, including internal oral features, chondrocranium, and hyobranchial apparatus, along with its advertisement call and natural history notes. This is the first description of the chondrocranium and hyobranchial apparatus for a member of the genus Bokermannohyla. The larval external morphology of B. ahenea is similar to those of other species of the B. circumdata group, but it can be distinguished from those of other species of the genus by its oral apparatus. The advertisement call of B. ahenea is complex with many numbers of notes. Also, spectral and temporal parameters of the advertisement call can be used to distinguish B. ahenea from its congeners.
Keywords: Bioacoustics; Brazilian Atlantic Forest; Chondrocranium; Larval morphology; Serra da Bocaina National Park